Identifikasi Keanekaragaman Jenis Ikan Hasil Tangkapan Nelayan Tapak Paderi Kota Bengkulu - Ayub Sugara Ayub; Ami Nolisa; Ari Anggoro; An Nisa Nurul Suci; Risnita Tri Utami; Yudho Andika; Feri Nugroho; Rifi Suhendri (Samakia : Jurnal Ilmu Perikanan, 2022)
Indonesian mainland waters have a high diversity of fish species, so they are listed as one of the waters with mega biodiversity in Indonesia. One of the efforts in managing fishery resources in a sustainable manner as mandated in Law No. 31 of 2009 concerning Fisheries, requires data and information about the types and morphology of fish in a waters. The purpose of this study was to determine and identify the type and morphology of fish caught by fishermen from Tapak Paderi Beach, Bengkulu City. The benefit of this research is to provide information about the types and morphology of fish caught by the Tapak Paderi fishermen in Bengkulu City. The technique used in sampling is the method of sample collection used is random sampling, marine fish samples are taken at random directly from the fishermen of Tapak Paderi. Identification is carried out by calculating the total length, standard length, identification begins with observing and noting the morphology of marine fish, including: color, mouth position, body shape, scale type, tail fin shape, type and number of spines on each fin. Based on the results of the research obtained, it was successful to take an inventory of 12 types of marine fish caught by fishermen at Tapak Paderi Beach, Bengkulu City